Morphological rearrangement of the metabolic link of the microcirculatory bed of guinea pigs lungs after sensitization with ovalbumin - Popko, S. S.; Попко, Світлана Сергіївна; Попко, С. С. (Запорізький державний медичний університет, 2021)
The reaction of the lung microvessels is an urgent issue of morphology and medicine in general, as well as one of the insufficiently investigated points in the study of morphological changes in chronic allergic diseases of the respiratory system. The aim is to study the morphological changes in the vessels of the metabolic link of the microcirculation in the lungs of guinea pigs sensitized with ovalbumin. Materials and methods. We have studied the lungs of 48 guinea pigs, using histological and morphometric methods, under conditions of experimental ovalbumin-induced allergic inflammation, simulated by three-time subcutaneous sensitization and subsequent 8-day intranasal inhalation of ovalbumin. To estimate the structural and functional state of capillaries, the inner diameter of the vessels was determined. Results. A general regularity in the reactivity of the hemomicrocirculatory bed of guinea pig lungs in experimental ovalbumin-induced allergic inflammation was established, which consists in a significant structural and functional restructuring of the exchange vessels of the microcirculatory bed. Dysfunction of the capillaries endothelium is manifested by a change of vasodilatation to vasospasm, as evidenced by morphometric changes in the diameter of the capillaries lumen in the experimental groups, and an increase in the permeability of the capillaries wall, which is confirmed by edema and disorganization of the connective tissue component. Conclusions. Allergic inflammation leads to structural and functional reorganization of the metabolic link of the hemomicrocirculatory bed of guinea pig lungs, which has a multidirectional staging character depending on the duration of the experiment and is a manifestation of a violation of the compensatory-adaptive processes of hemomicrocirculation. The most pronounced changes in the form of a decrease in the diameter of the lumen of the blood capillaries of the lungs of guinea pigs by 23 % compared to the control are observed during the late period of the development of the allergic inflammatory process.

Актуальною проблемою морфології та медицини, а також одним із недостатньо досліджених явищ у вивченні морфологічних змін під час хронічних алергічних захворювань дихальної системи залишається реакція мікросудин легень. Мета роботи – вивчити морфологічні зміни судин обмінної ланки гемомікроциркуляторного русла легень морських свинок, сенсибілізованих овальбуміном. Матеріали та методи. За допомогою гістологічного, морфометричного методів вивчили легені 48 самців морської свинки в умовах експериментального овальбумін-індукованого алергічного запалення, яке моделювали шляхом триразової підшкірної сенсибілізації та наступної 8-денної інтраназальної інгаляції овальбуміном. Для визначення структурної та функціональної перебудови кровоносних капілярів установлювали величину внутрішнього діаметра судин. Результати. Встановили загальну закономірність реактивності мікроциркуляторного русла легень морських свинок при експериментальному овальбумін-індукованому алергічному запаленні, що полягає в суттєвій структурно-функціональній перебудові судин обмінної ланки мікроциркуляторного русла легень морської свинки. Так, виявили ознаки дисфункції ендотелію кровоносних капілярів: зміну дилатації судин на стійкий спазм, про що свідчили морфометричні зміни діаметра просвіту капілярів в експериментальних групах, а також збільшення проникності судинної стінки, що підтверджують набряк і дезорганізація сполучнотканинного компонента і строми. Висновки. Алергічне запалення призводить до структурної та функціональної реорганізації обмінної ланки мікроциркуляторного русла легень морських свинок, що має різноспрямований стадійний характер залежно від тривалості експерименту та є проявом порушення компенсаторно-адаптаційних процесів гемомікроциркуляції. Найбільше виражені зміни, а саме зменшення діаметра просвіту кровоносних капілярів легень морських свинок на 23 % порівняно з контролем виявили протягом пізнього періоду розвитку алергічного запального процесу.

Актуальной проблемой морфологии и медицины, а также одним из недостаточно исследованных явлений в изучении морфологических изменений при хронических аллергических заболеваниях дыхательной системы остается реакция микрососудов легких. Цель работы – изучить морфологические изменения сосудов обменного звена микроциркуляторного русла легких морских свинок, сенсибилизированных овальбумином. Материалы и методы. С помощью гистологического, морфометрического методов изучили легкие 48 самцов морской свинки в условиях экспериментального овальбумин-индуцированного аллергического воспаления, которое моделировали путем трехкратной подкожной сенсибилизации и последующей 8-дневной интраназальной ингаляции овальбумином. Для определения структурной и функциональной перестройки кровеносных капилляров определяли величину внутреннего диаметра сосудов. Результаты. Установлена общая закономерность реактивности гемомикроциркуляторного русла легких морских свинок при экспериментальном овальбумин-индуцированном аллергическом воспалении, заключающаяся в существенной структурно-функциональной перестройке сосудов обменного звена микроциркуляторного русла легких морской свинки. Так, обнаружены признаки дисфункции эндотелия кровеносных капилляров: изменение дилатации сосудов на стойкий спазм, о чем свидетельствуют морфометрические изменения диаметра просвета капилляров в экспериментальных группах, а также увеличение проницаемости сосудистой стенки, что подтверждают отек и дезорганизация соединительнотканного компонента стромы. Выводы. Аллергическое воспаление приводит к структурной и функциональной реорганизации обменного звена гемомикроциркуляторного русла легких морских свинок, которая носит разнонаправленный стадийный характер в зависимости от продолжительности эксперимента и является проявлением нарушения компенсаторно-адаптационных процессов гемомикроциркуляции. Наиболее выраженные изменения в виде уменьшения диаметра просвета кровеносных капилляров легких морских свинок на 23 % по сравнению с контролем отмечены в течение позднего периода развития аллергического воспалительного процесса.
Морфологічна перебудова обмінної ланки мікроциркуляторного русла легень морських свинок після сенсибілізації овальбуміном
Морфологическая перестройка обменного звена микроциркуляторного русла лёгких морских свинок после сенсибилизации овальбумином
Попко С. С. - ORCID ID: 0000-0002-5533-4556
Keywords: capillary; microcirculation; experimental allergic inflammation; lung; ovalbumin; guinea pig; кровоносний капіляр; мікроциркуляція; експериментальне алергічне запалення; легеня; овальбумін; морська свинка; кровеносный капилляр; микроциркуляция; экспериментальное аллергическое воспаление; легкое; овальбумин; морская свинка